Gluten serological testing in various dog breeds with paroxysmal dyskinesia - Rogers, Casey B.; Meyerhoff, Nina; Volk, Holger A. (Frontiers in Veterinary Science, 2023)
Background: Paroxysmal gluten-sensitive dyskinesia is a subtype of movement disorder classified as canine paroxysmal dyskinesia (cPD) which has only been described in Border Terriers (BT). Objectives: Our aim was to report cPD with positive gluten serology in dog breeds other than BT. Animals: Thirty-one client owned dogs with suspected cPD. Methods: Hospital records of dogs where serum was tested for Modified Gliadin Peptide immunoglobulin G (Gliadin IgG) and Tissue Transglutaminase-2 immunoglobulin A (Transglutaminase-2 IgA) were studied. Thirty-one dogs were presented to the clinic with cPD. A work-up consistent with Tier 1 or Tier 2 confidence level for canine epilepsy was undertaken in all dogs. The dogs’ diets and episode description or videos in 16/31 cases were additionally studied. A follow-up was held to inquire on the dogs’ wellbeing and response to diet change. Results: Fourteen of thirty-one dogs were tested positive for gluten-sensitivity with Gliadin IgG or Transglutaminase-2 IgA or both ratios elevated. In seven dogs, serology was classified as questionable with Gliadin IgG or Transglutaminase ratios mildly elevated. Ten dogs tested negative. According to the owners’ reports five of the dogs which tested positive had no more episodes after changing to a strictly gluten free diet, with one of the dogs relapsing twice after being fed gluten containing treats. Three dogs had a reduction in episode frequency of >50% and two dogs show shorter and less intense episodes. Conclusion: A considerable subset of dog breeds with presumed cPD shows laboratory signs of gluten sensitivity and response to gluten-free diets.